Comparing the Prospective Effect of Judicial Rulings Across Jurisdictions - Steiner, Eva (Springer, 2016)
This work deals with the temporal effect of judicial decisions and more specifically, with the hardship caused by the retroactive operation of overruling decisions. By means of a jurisprudential and comparative analysis, the book explores several issues created by the overruling of earlier decisions.